The Influence of Work-Life Balance, Compensation Systems, and Technological Support on Employee Loyalty, with Job Satisfaction as an Intervening Variable (An Empirical Study of Employees at The J&T Express Branch in Sukmajaya, Depok) - Intan Azimatul Iffah; Corry Yohana; Christian Wiradendi (Return : Study of Management, Economic and Bussines, 2026)
Digital transformation in the logistics industry has increased operational demands and created challenges in maintaining employee loyalty due to workload pressures, technological adaptation requirements, and evolving employee expectations. This study aims to examine the influence of work-life balance, compensation systems, and technological support on employee loyalty, with job satisfaction as an intervening variable, among employees at the J&T Express Sukmajaya Branch, Depok. This research employed a quantitative approach with an explanatory research design. Data were collected through questionnaires distributed to 150 employees using a census sampling technique and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The results indicate that work-life balance, compensation systems, and technological support have positive and significant effects on job satisfaction and employee loyalty. Furthermore, job satisfaction significantly mediates the relationship between the independent variables and employee loyalty. The findings reveal that job satisfaction is the most dominant factor influencing employee loyalty. This study concludes that improving employee-centered management practices through balanced work arrangements, fair compensation systems, and effective technological support can strengthen employee loyalty and enhance organizational sustainability.